Desarrollo de un software para la calibración del sistema térmico y gravimétrico de un motor de combustión interna (2023)
The work carried out focused on the development of software programmed in the C# language. The basis of this project was a previous investigation that focused on evaluating the metrological reliability of the thermal and gravimetric system of the internal combustion engine.